Pelatihan pembuatan briket arang kelapa bagi calon lulusan SLTA di Pengalihan Keritang, Indragiri Hilir, Riau - Sugiono, Nana; Ihwan, Khairul; Surya, Roberta Zulfhi (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The initiative to process coconut shell charcoal emerged as some farmers began selling coconuts as copra, leaving the shells available for charcoal production. However, further processing into coconut shell charcoal briquettes—which offer higher economic value—remains limited. Twelfth-grade high school students (aged 17–19) are in a transitional phase toward employment or higher education, requiring the provision of practical skills. A skills training program on coconut charcoal briquette production was held in January 2025 at SMA Karya Pengalihan Keritang, involving 40 students. The training included hands-on briquette making and business economic analysis. This activity aimed to provide entrepreneurial experience and enhance job readiness. The expected impact is that participants will recognize the economic potential of briquette production as a viable business opportunity, given the high profit margins between production costs and market prices.